The Influence of Using Smartphone to Interesting Learning and GPA in Students at Physics Education Department - Anggini Mutia Suwa; A Halim; Zainuddin Zainuddin (Asian Journal of Science Education, 2020)
Research using a quantitative descriptive approach aims to determine the effect of smartphone usage on learning interest and GPA of Physics Education students at Universitas Syiah Kuala. The samples in this study were all physics students in academic year 2016 and 2017. Data collection was obtained by using a questionnaire for smartphone usage and interest in learning, while documentation for student GPA. Data processing using percentage analysis and multiple linear regression test. The results of the statistical test show that there was an influence of the use of smartphones on student interest and GPA. It was obtained that the calculated rcount was greater than rtable that was equal to 17.38. Keywords: Influence, Smartphone Usage, Interests and GPA